Research and use of phytase in poultry farming - Sanmiguel Plazas, Rosa Angélica (Spei Domus, 2011)
The main end products of poultry farming are chicken meat and eggs for human consumption, which require, in addition to high financial performance, the development of strategies to ensure food security and reduce environmental impact. Given that many studies report the use of phytase in monogastric diets as an environment friendly and profitable practice, the present review intends to compile the most significant data generated in recent years, seeking to identify the main factors of production performance that are either positively or negatively affected by endogenous phytase activity, as well as the microbial and physiological reasons for which this activity has been deemed a promising element that reduces environmental costs generated by the poultry industry. Most of the consulted sources agree on favorable results in weight gain, egg production rate and decreased phosphorus in excreta upon adding phytase to diets low on nonphytate phosphorus (npp). However, food conversion, egg weight and the specific density of eggs do not suffer any changes with the addition of phytase to the diet.